Analysis of environmental externalities from colombian transportation (2018)
From an environmental and economic efficiency perspective, transportation is a sector of major interest in Colombia, in particular considering its contribution in terms of atmospheric pollution and time losses due to congestion. By the use of different approaches, this research seeks to identify, evaluate and propose instruments to reduce negative impacts from the transport sector. We offer two contributions. First, we present an economic model for the transport sector of Bogotá. This is a partial equilibrium representation of the transport market in a typical corridor to look for alternative policy mixes that produce social welfare gains. This model allows estimating the efficiency of different policy instruments to address the major externalities (congestion, air pollution). We considered options such as pricing instruments, alternatives for the public transport operation and environmental regulation. Second, we offer an analysis of the potential and costs of reducing GHG emissions for the transport sector of Colombia